PENINGKATAN PENDAPATAN MASYARAKAT DESA PULO RUNGKOM MELALUI PERTANIAN INTENSIF - Lindawati Lindawati; Sri Wahyuni; Maisun Maisun; Muthaharah Muthaharah (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Indonesia was once known agrarian country because the large numbers of its inhabitants earned as farmers. In any case, this country has possibly lose the farmers, this is because of low income form agricultural products, thereby causing change shaping in work. The cause of decline in agricultural sector is the agricultural sector is considered less prestigious and does not provide guarantess for income. Hence, effort are needed to keep agricultural production running and have the option to make an expansion in farmers income by apllying minapadi cultivation agricultural technology. The purpose for this activity is to acquaint technology agriculture to increase income the community. Activities are carried out using the village community empowerment methode and the activity implementation. The targets are farmers, traders, youth organization and representatives of PKK. The outcome acquired are the arrangement of joint business and increment the income of farmers.